A Lyapunov functional for a system with a time-varying delay - Duda, Józef (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a method to determine a Lyapunov functional for a linear time-invariant system with an interval timevarying delay. The functional is constructed for the system with a time-varying delay with a given time derivative, which is calculated on the system trajectory. The presented method gives analytical formulas for the coefficients of the Lyapunov functional.
Keywords: Lyapunov functional; time delay system; LTI system